2010
DOI: 10.4236/as.2010.13012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Cuban endemism Carica cubensis Solms using random amplified polymorphic DNA (RAPD) markers

Abstract: The objective of this work is to present an appropriate set of RAPD (random amplified polymorphic DNA) markers using single and multiplex PCR analysis suitable for the characterization of the endemic Cuban species Carica cubensis and the establishment of genetic relationships with the cultivated species Carica papaya. RAPD markers presented a high level of polymorphism. In addition, the incorporation of more than one RAPD primer in the PCR analysis increased the number of obtained bands and the polymorphism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Among the molecular markers, RAPD and ISSR markers have been extensively used to study genetic diversity and relationships in papaya germplasm (Rodríguez et al, 2010;Sudha et al, 2013). Among these molecular markers, ISSRs are considered useful and have been extensively used for the identification of species or germplasms in a wide range of plants (Ahmad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the molecular markers, RAPD and ISSR markers have been extensively used to study genetic diversity and relationships in papaya germplasm (Rodríguez et al, 2010;Sudha et al, 2013). Among these molecular markers, ISSRs are considered useful and have been extensively used for the identification of species or germplasms in a wide range of plants (Ahmad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular markers, including random amplified polymorphic DNA (RAPD), intersimple sequence repeat (ISSR), and amplified fragment length polymorphism (AFLP), have been used for analysis of genetic diversity, relationships, and germplasm identification of papaya (de Jesus et al, 2013). Among the molecular markers, RAPD and ISSR markers have been extensively used to study genetic diversity and relationships in papaya germplasm (Rodríguez et al, 2010;Sudha et al, 2013). Among these molecular markers, ISSRs are considered useful and have been extensively used for the identification of species or germplasms in a wide range of plants (Ahmad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…La ubicación geográfica y aislamiento de la zona prospectada, el tipo de reproducción, los resultados de la caracterización molecular (Rodríguez et al, 2010) y la caracterización morfoagronómica en condiciones tradicionales de cultivo, indican que el papayo silvestre identificado constituye una población.…”
Section: Discussionunclassified
“…The polymorphisms obtained from the analysis of these genotypes of C. papaya were more numerous than the 186 polymorphisms found by Kim et al (2002), when analyzing 63 papaya accessions with this same type of molecular marker. Moreover, Rodríguez et al (2010) reported only 45 polymorphic bands using nine RAPD primers when assessing the genetic diversity of the species Vasconcellea cubensis and C. papaya. Table 3.…”
Section: Characterization With Aflp Markersmentioning
confidence: 99%
“…Due to their many advantages, especially high polymorphism, reproducibility and wide genomic coverage in many species, amplified fragment length polymorphism (AFLP) markers have been used to characterize molecular diversity and to establish fingerprinting in various species (Kim et al, 2002, Rodríguez et al, 2010. Inter-simple sequence repeat (ISSR) markers constitute another PCR-based technique useful for genome studies.…”
Section: Introductionmentioning
confidence: 99%